Cell sorting enables interphase fluorescence in situ hybridization detection of low BCR‐ABL1 producing stem cells in chronic myeloid leukaemia patients beyond deep molecular remission. (January 2014) - van, Peter B.; Petersen, Charlotte C.; Nyvold, Charlotte G.; Ommen, Hans B.; Roug, Anne S.; Nederby, Line; Hokland, Peter; Kjeldsen, Eigil
Summary The exact disease state of chronic myeloid leukaemia (CML) patients in deep molecular remission is unknown, because even the most sensitive quantitative reverse transcription polymerase chain reaction (qPCR) methods cannot identify patients prone to relapse after treatment withdrawal. To elucidate this, CD34+ stem cell and progenitor cell subpopulations were isolated by fluorescence‐activated cell sorting (FACS), and their content of residual Philadelphia positive (Ph+) cells was evaluated in 17 CML patients (major molecular response, n = 6; 4‐log reduction in BCR‐ABL1 expression (MR4), n = 11) using both sensitive qPCR and interphase fluorescence in situ hybridization (iFISH). Despite evaluating fewer cells, iFISH proved superior to mRNA‐based qPCR in detecting residual Ph+ stem cells (P = 0·005), and detected Ph+ stem‐ and progenitor cells in 9/10 patients at frequencies of 2–14%. Moreover, while all qPCR+ samples also were iFISH+, 9/33 samples were qPCR‐/iFISH+, including all positive samples from MR4 patients. Our findings show that residual Ph+ cells are low BCR‐ABL1 producers, and that DNA‐based methods are required to assess the content of persisting Ph+ stem cells in these patients. This approach demonstrates a clinically applicable manner of assessing residual disease at the stem cell level in CML patients in MR4, and may enable early and safe identification of candidates for tyrosine kinase inhibitor withdrawal.